Visual outcomes of the surgical rehabilitative process following open globe injury repair - Sather, Richard N.; Molleti, Sanjana; Moon, Jade Y.; Chaudhry, Saliha; Montezuma, Sandra R.; Simmons, Michael (Frontiers in Ophthalmology, 2024)
Background: The path of rehabilitation of an eye after open globe injury (OGI) may require multiple additional secondary surgeries after the initial repair. Although much has been studied regarding the outcomes of secondary surgeries after open globe repair, it can be challenging to understand the possible implications of the surgical rehabilitative process. This retrospective study considers the benefits of the required additional secondary surgeries for a consecutive series of OGI patients. Methods: OGI patients who had at least one additional surgery after the initial open globe repair (OGR) were studied retrospectively. Additional inclusion criteria included: follow up of at least 12 months since the initial injury and at least 3 months since their most recent surgery, and no additional planned interventions. Preoperative visual acuity was compared to final visual acuity. Additionally, the odds of achieving ambulatory vision (≥20/800) and reading vision (≥20/40) were calculated after each indicated consecutive surgery. Results: A cohort of 74 eyes from 73 patients met our inclusion criteria. These patients underwent a mean of two additional surgeries. The mean logMAR VA improved from 2.3 (HM) at presentation to 1.4 (20/150), or a 9-line Snellen equivalent improvement. Upon reaching their final visit status, 50% of patients had achieved ambulatory vision and 30% of patients had achieved reading vision. The odds of achieving ambulatory vision after completion of all the rehabilitative surgical process compared to the vision prior to the secondary rehabilitative surgery were higher (OR: 19.1, 95% CI: 7.9 – 30.4, p = 0.0008) as were the odds of achieving reading vision (OR: 4.6, 95% CI: 0.2 – 9.0, p = 0.04). With subsequent second, third, and fourth additional surgeries, the odds of achieving either ambulatory or reading vision at the final visit compared to their preoperative visual acuities were not significant (p > 0.05) but the visual acuity continued to trend toward visual improvement. Conclusions: Approximately 50% individuals who required additional surgery at UMN achieved ambulatory vision and 30% achieved reading vision. The odds of visual improvement through the surgical rehabilitative process were very high, with the greatest gains generally achieved after the first surgery.